How to make an apple pie and see the world - Priceman, Marjorie (New York : Knopf : Distributed by Random House, 1994)
Since the market is closed, the reader is led around the world to gather the ingredients for making an apple pie. Includes recipe.
Wilson's Children.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
3.5
K-3
Keywords: Pies -- Fiction; Food -- Fiction; Voyages and travels -- Fiction; Humorous stories; Pies -- Fiction; Food -- Fiction; Voyages and travels -- Fiction; Humorous fiction; Pies -- Fiction; Food -- Fiction; Voyages and travels -- Fiction; Humorous stories